2018
DOI: 10.1148/radiol.2017170094
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Carotid Web in Patients with Acute Intracranial Stroke Due to Intracranial Large Vessel Occlusion

Abstract: Purpose To investigate the prevalence of symptomatic carotid web in patients with acute ischemic stroke due to intracranial large vessel occlusion, to determine the clinical and imaging profile of patients with carotid web as well as their association with ischemic stroke, and to determine the interobserver agreement in the assessment of carotid webs. Materials and Methods All patients (n = 500) of the Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
73
3
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 19 publications
5
73
3
6
Order By: Relevance
“…HR-MRI enables visualization of the webs that are small, thin, membranous, filamentous, or diaphragm-like 3,4. A recent large acute stroke trial reported carotid web on the symptomatic side in 2.5% of patients 5. In an ongoing prospective study of HR-MRI in patients with >50% symptomatic carotid stenosis, we observed carotid webs of various morphologies in about 22%.…”
mentioning
confidence: 66%
“…HR-MRI enables visualization of the webs that are small, thin, membranous, filamentous, or diaphragm-like 3,4. A recent large acute stroke trial reported carotid web on the symptomatic side in 2.5% of patients 5. In an ongoing prospective study of HR-MRI in patients with >50% symptomatic carotid stenosis, we observed carotid webs of various morphologies in about 22%.…”
mentioning
confidence: 66%
“…Herein, we describe a case of acute ischemic stroke due to right MCA occlusion with an ipsilateral carotid web. From a clinical perspective, the following important points in our case deserve discussion: 1) a carotid web without any evidence of cardioembolism or large artery atherosclerosis could be the sole source of brain embolism, which necessitates endovascular mechanical thrombectomy; 4 2) a carotid web after acute ischemic stroke could be a source of recurrent embolism with reemergence of newly formed thrombus around the web, especially in cases not treated with antithrombotics during the acute phase of stroke because of the risk of hemorrhage; and 3) serial follow-up neurosonologic examinations, which are simple and readily accessible, could be an important diagnostic tool for decision making on the timing of antithrombotic use because a carotid web has an early dynamic course from innocent web to superimposed thrombosis.…”
Section: Discussionmentioning
confidence: 98%
“…2 In the subanalysis of the multicenter randomized trial of endovascular treatment for acute ischemic stroke in the Netherlands (MR CLEAN) trial, the incidence of carotid web was 2.5% ipsilateral to index stroke. 4 However, the serial imaging depiction of the carotid web was not well reported because of its rarity in clinical practice and the limited availability of repeated imaging acquisition. Herein, we report serial imaging findings of carotid web, using ultrasonography, which is the simplest and easily accessible imaging modality, to depict the natural course of the superimposed thrombosis in the carotid web with anticoagulant therapy.…”
mentioning
confidence: 99%
“…3,4 A recent large acute stroke trial reported carotid web on the symptomatic side in 2.5% of patients. 5 In an ongoing prospective study of HR-MRI in patients with >50% symptomatic carotid stenosis, we observed carotid webs of various morphologies in about 22%. Various protocols may help with in-depth evaluation of carotid web morphology, composition, as well as associated hemodynamic alterations.…”
mentioning
confidence: 89%